Cyclical dynamics and the gender pay gap: A structural VAR approach - Kovalenko, Tim; Töpfer, Marina (Economic Modelling, 2021)
Gender pay gaps persist worldwide despite political emphasis to close them. The literature found various drivers of the gaps but remained vastly silent about the role of cyclical dynamics. Using quarterly US data over the period 1979-2019, we study the effects of cyclical dynamics on the gender pay gap based on a structural vector auto-regression model with zero and sign restrictions. The results suggest that technology shocks lead to lower levels of the gender pay gap in the medium run, while higher wage bargaining power reduces the gap in the short run. However, these reductions of the gap come at the cost of increased unemployment. As a policy implication, these results imply a trade-off between lower gender pay gaps and higher unemploymen
Keywords: Gender pay gap; Vector Auto-Regression(VAR) model; Cyclical dynamics; Macroeconomic shocks; Gender

Is the German Labor Market Granular? - Kovalenko, Tim; Schnabel, Claus; Stüber, Heiko (Applied Economics Letters, 2020)
This paper is the first to investigate the relevance of the ‘granular hypothesis” proposed by Gabaix (Econometrica 2011) for employment growth. Using comprehensive data for Germany, we show that the establishment size distribution in terms of employment is indeed fat-tailed and that idiosyncratic shocks to large establishments explain a substantial portion of aggregate employment change. This relationship is more pronounced in the manufacturing than the service sector. Our findings may be an argument for stabilizing the largest establishments when hit by negative idiosyncratic shocks, since their employment fluctuations could spill over to aggregate employment growt
Keywords: Idiosyncratic shocks; granular residual; employment; administrative data

Uncertainty shocks and employment fluctuations in Germany: the role of establishment size - Kovalenko, Tim (Oxford Economic Papers, 2023)
Uncertainty shocks are found to affect labour market outcomes adversely. Most studies interrelate non-convex labour adjustment costs with the propagation of macroeconomic uncertainty to the labour market. I show that non-convex labour adjustment costs differ by establishment size in Germany. Hence, uncertainty shocks should affect large and small establishments differently. Therefore, this article studies the effects of uncertainty shocks on employment adjustments in large and small establishments employing four structural vector auto-regressive models for Germany from 1992 to 2014. These four models estimate the effects of uncertainty shocks on employment, worker flows, job flows, as well as worker churn in establishments with fewer than 100 and with at least 100 employees. The results suggest that uncertainty shocks trigger considerable employment fluctuations in large establishments while they barely affect small establishments. Furthermore, large establishments adjust their labour input by delaying the replacement of workers.
CRIS-Team WoS Importer:2023-05-12